2020
DOI: 10.1002/mma.6926
|View full text |Cite
|
Sign up to set email alerts
|

Discrete Chebyshev polynomials for nonsingular variable‐order fractional KdV Burgers' equation

Abstract: In this article, nonlinear variable-order (VO) fractional Korteweg-de Vries (KdV) Burgers' equation with nonsingular VO time fractional derivative is introduced and discussed. The approximate solution of the expressed problem is obtained in the form of a series expansion in terms of the shifted discrete Chebyshev polynomials (CPs) with great accuracy. The method is a computational procedure based on the collocation technique and the shifted discrete CPs together with their operational matrices (ordinary and VO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The advantage of this method is that it provides a global solution to the problem. At the same time, the accuracy and effectiveness of the method are proved by numerical problems 30 . Hosseininia et al 31 introduced the two‐dimensional Kuramot‐Sivashinsky equation of variable fractional order and used the two‐dimensional Chebyshev cardinal functions (CCFs) to give a semi‐discrete method to solve the equation.…”
Section: Introductionmentioning
confidence: 99%
“…The advantage of this method is that it provides a global solution to the problem. At the same time, the accuracy and effectiveness of the method are proved by numerical problems 30 . Hosseininia et al 31 introduced the two‐dimensional Kuramot‐Sivashinsky equation of variable fractional order and used the two‐dimensional Chebyshev cardinal functions (CCFs) to give a semi‐discrete method to solve the equation.…”
Section: Introductionmentioning
confidence: 99%
“…ese equations are highly nonlinear and describe wave structures in crystal lattice, plasma, water, and density stratified ocean waves, etc., that are explored by many researchers. Heydari et al observed fractional KdV-burger's equation by discrete Chebyshev polynomials [19], second order difference schemes for timefractional KdV-burger's is solved by Cen et al [20], fractional Kaup-Kupershmidt equation is analyzed by Shah et al [21], Iqbal et al [22] applied Atangana-Baleanu derivative on fractional Kersten-Krasil'shchik coupled KdV-mKdV system. KdV equations are also used in string theory with continuum limit.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, discrete polynomials have been extensively applied for solving diverse problems. For instances, see [39][40][41][42][43][44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%